Identification of HLA-A, HLA-B, and HLA-C triple homozygous and double homozygous donors: a path toward synthetic superdonor advanced therapeutic medicinal products - Naumovas, Daniel; Rojas-Araya, Barbara; Polanco, Catalina M.; Andrade, Victor; Čekauskienė, Rita; Valatkaitė-Rakštienė, Beatričė; Laurinaitytė, Inga; Jakubauskas, Artūras; Stoškus, Mindaugas; Griškevičius, Laimonas; Nalvarte, Ivan; Inzunza, Jose; et al. (Frontiers in Immunology, 2025)
Human-induced pluripotent stem cells with broad immune compatibility are highly desirable for regenerative medicine applications. Human leukocyte antigen (HLA) class I homozygous cell sources are ideal for immune compatibility modeling. Here, we profile HLA-A, HLA-B, and HLA-C alleles in 3,496 Lithuanian donors genotyped at three-field resolution. The five most frequent alleles constitute 74.6% of HLA-A, 43.2% of HLA-B, and 59.2% of HLA-C, with HLA-A*02:01:01, HLA-B*07:02:01, and HLA-C*07:02:01 being the most common. Lithuanian allele frequencies closely resemble those of European-American and British populations. We identified 153 double homozygotes and 51 triple homozygotes for HLA-A, HLA-B, and HLA-C. Compatibility modeling showed that triple homozygous profiles match 60.5% of Lithuanians, 13.4% of the British population, and 7.4% of European-Americans. CRISPR-Cas9 guide RNA design yielded 54 candidates predicted to disrupt HLA-A or HLA-B while preserving HLA-C, producing edited profiles matching over 97.9% of Lithuanians, 95.7% of European-Americans, and 95.5% of the British population. Finally, we established 15 fibroblast lines from triple homozygotes as a bioresource for the derivation of human-induced pluripotent stem cells and immune compatibility studies.